Internalisasi Nilai-Nilai Pendidikan Perspektif Abraham Maslow (1908-1970) (Analisis Filosofis) - Masbur Masbur (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2015)
Value for Maslow is the value of existence (being values), which includes among others: truth, goodness, beauty, full of energy, unique, perfection, fullness, justice, order, simplicity, rich nature, the full nature of the game and the nature of self- sufficient. These values will behave as needs and fulfillment will bear the psychological health and leads to the possibility of a peak experience. Moreover, according to Maslow value focus is on the role of human beings, human nature, and moral values. At the first show that the award of the inner potential and the human role in determining his choices. In the second explains that human nature lies in the nature that fosters inner porensi independence and responsibility on humanitarian grounds. The latter showed that moral values are values that are very important for people to develop themselves. The implication of all it is the first, the realization of development opportunities and the role of human psychological behavior-based humanistic and religious. Second, the realization of psychological behavior improvement opportunities based on the transcendental spiritual and scientific aspects. Third, the realization of development opportunities of building science concerned with the aspect of morality. Because for him, the peak experience is becoming more of yourself, realizing his ability to perfect, closer to the core of its existence, and more fully as a human being and experience the peak is at the core of religion. Nilai bagi Maslow adalah nilai keberadaan (being values), yang mencakup diantaranya adalah: kebenaran, kebaikan, keindahan, penuh energi, unik, kesempurnaan, kepenuhan, keadilan, ketertiban, kesederhanaan, sifat kaya, sifat penuh permainan dan sifat mencukupi diri. Nilai-nilai tersebut akan berprilaku seperti kebutuhan dan pemenuhannya akan melahirkan kesehatan psikologis dan membawa ke arah kemungkinan pengalaman puncak. Selain itu, fokus nilai menurut Maslow adalah pada peran manusia, hakikat manusia, dan nilai moral. Pada yang pertama menunjukkan bahwa pemberian penghargaan terhadap potensi batin dan peran manusia dalam menentukan pilihan-pilihannya. Pada yang kedua menerangkan bahwa hakikat manusia terletak pada porensi batin yang menumbuhkan sifat kemandirian dan tanggung jawab atas dasar kemanusiaan. Sedangkann yang terakhir menunjukkan bahwa nilai moral adalah nilai yang sangat penting bagi manusia untuk mengembangkan dirinya. Implikasi dari semua itu adalah pertama, terwujudnya peluang pengembangan peran manusia dan tingkah laku psikologisnya yang berbasis humanistik dan religious. Kedua, terwujudnya peluang penyempurnaan tingkahlaku psikologis yang berlandaskan pada aspek spiritual transendental dan ilmiah. Ketiga, terwujudnya peluang pengembangan bangunan ilmu yang menaruh perhatian pada aspek moralitas. Karna baginya, pengalaman puncak adalah menjadi lebih dari diri sendiri, lebih mewujudkan kemampuannya dengan sempurna, lebih dekat inti keberadaannya, dan lebih penuh sebagai manusia dan pengalaman puncak itu ada pada inti agama. Kata Kunci : Internalisasi. Nilai Pendidikan Abraham Maslow